Finite Element Modeling of Shunt Reactors Used in High Voltage Power Systems - Minh, T. P.; Duc, H. B.; Hoai, N. P.; Cong, T. T.; Cong, M. B.; Thanh, B. D.; Quoc, V. D. (Engineering, Technology & Applied Science Research, 2021)
Shunt reactors are important components for high-voltage and extra high voltage transmission systems with large line lengths. They are used to absorb excess reactive power generated by capacitive power on the lines when no-load or under-load occurs. In addition, they play an important role in balancing the reactive power on the system, avoiding overvoltage at the end of the lines, and maintaining voltage stability at the specified level. In this paper, an analytical method based on the theory of magnetic circuit model is used to compute the electromagnetic fields of shunt reactors and then a finite element method is applied to simulate magnetic field distributions, joule power losses, and copper losses in the magnetic circuit. In order to reduce magnetic flux and avoid magnetic circuit saturation, it is necessary to increase the reluctance of the magnetic circuit by adding air gaps in the iron core. The air gaps are arranged along the iron core to decrease the influence of flux fringing around the air gap on shunt reactors' total loss. Non-magnetic materials are often used at the air gaps to separate the iron cores. The ANSYS Electronics Desktop V19.R1 is used as a computation and simulation tool in this paper.